International Migration, Remittances, and Poverty in Developing Countries - Adams, Richard H., Jr. (World Bank, Washington, DC, 2014)
Few studies have examined the impact of international migration and remittances on poverty in a broad cross-section of developing countries. The authors try to fill this gap by constructing a new data set on poverty, international migration, and remittances for 74 low- and middle-income developing countries. Four key findings emerge: 1) International migration-defined as the share of a country's population living abroad-has a strong, statistical impact in reducing poverty. On average, a 10 percent increase in the share of international migrants in a country's population will lead to a 1.9 percent decline in the share of people living in poverty ($1.00 a person a day). 2) Distance to a major labor-receiving region-like the United States or OECD (Europe)-has an important effect on international migration. Developing countries that are located closest to the United States or OECD (Europe) are also those countries with the highest rates of migration. 3) An inverted U-shaped curve exists between the level of country per capita income and international migration. Developing countries with low or high per capita GDP produce smaller shares of international migrants than do middle-income developing countries. The authors find no evidence that developing countries with higher levels of poverty produce more migrants. Because of considerable travel costs associated with international migration, international migrants come from those income groups which are just above the poverty line in middle-income developing countries. 4) International remittances-defined as the share of remittances in country GDP-have a strong, statistical impact in reducing poverty. On average, a 10 percent increase in the share of international remittances in a country's GDP will lead to a 1.6 percent decline in the share of people living in poverty.